(untitled) (Communications in Computational Physics, 2025)
A central-moment discrete Boltzmann method (CDBM) is proposed for reactive flows, accommodating adjustable specific heat ratios and Prandtl numbers. In the framework of CDBM, a unified set of kinetic equations is used to delineate both macroscopic quantities and higher-order central moments. Via these central moments, the nonequilibrium effects that are directly related to the thermal fluctuation beyond conventional hydrodynamic governing equations can be quantified. Moreover, the discrete Boltzmann equation of the CDBM is simpler than that of previous multiple-relaxation-time DBMs, owing to the elimination of the additional term in the DBM. Furthermore, this method is capable of modeling supersonic compressible reactive flows characterized by high Mach numbers. The model is verified through simulations encompassing sound waves, shock waves, thermal Couette flows, regular shock reflections, and supersonic reactive waves.